The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11095-010-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Mechanism Studies of Cationic Chitosan-Modified Biodegradable PLGA Nanoparticles for Efficient siRNA Drug Delivery

Abstract: This study suggests that biodegradable cationic CHT-PLGA nanoparticles possess great potential for efficient and safer siRNA delivery in future clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 40 publications
1
36
0
2
Order By: Relevance
“…It has been reported that cationic polymers, such as polyethyleneimine and poly-L-lysine hydrobromide, can be used as candidate materials to modify PLGA nanoparticles for gene or drug delivery. [10][11][12][13] Among these, chitosan seems to be the most suitable adjuvant due to its biodegradable and biocompatible, mucoadhesive, and permeability-enhancing properties. 14,15 Mucus adhesion can prolong the duration of interaction between drugs and cells, while increased tissue permeability can allow dissemination of drugs through the paracellular transport pathway, via the opening of tight junctions between epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cationic polymers, such as polyethyleneimine and poly-L-lysine hydrobromide, can be used as candidate materials to modify PLGA nanoparticles for gene or drug delivery. [10][11][12][13] Among these, chitosan seems to be the most suitable adjuvant due to its biodegradable and biocompatible, mucoadhesive, and permeability-enhancing properties. 14,15 Mucus adhesion can prolong the duration of interaction between drugs and cells, while increased tissue permeability can allow dissemination of drugs through the paracellular transport pathway, via the opening of tight junctions between epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, PLGA has a negative charge, which limits its interaction with DNA/RNA, so cationic compounds have been combined with this polymer in order to condense genetic material efficiently. 17,18 For example, chitosan, a polysaccharide used widely in the pharmaceutical field because of its biocompatibility, biodegradability, safety, and mucoadhesive properties, 19,20 has been used in combination with PLGA in order to increase transfection efficiency. 21,22 In 2007, Nafee et al investigated the variation in physicochemical parameters of PLGA/high molecular weight chitosan nanoparticles (produced by the emulsion-diffusionevaporation technique) as a function of the proportions of compounds contained therein.…”
mentioning
confidence: 99%
“…Therefore, a considerable amount of work has been documented on the loading efficiency of siRNA on polymers but very few have loaded siRNA on chitosan nanoparticles as a bioadhesive, biocompatible, and biodegradable polymer with unique gene delivery properties [2]. The efficacy of siRNA loaded carriers (i.e., gene silencing) has been reported to significantly increase with increasing the siRNA loading [3].…”
mentioning
confidence: 99%
“…The salt form of chitosan [4], concentration of chitosan in chitosan-poly(lactic-co-glycolic acid) nanoparticles [3] and insertion of 1,2-dioleoyl-3-trimethylammonium-propane [5] and tripolyphosphate [6] as ionic agents, have been reported to affect the loading efficiency of chitosan nanoparticles as carriers of siRNA. However, the above-mentioned studies have only reported a very limited number of experiments without providing a comprehensive understanding about factors influencing the loading efficacy in an siRNA/polymer system.…”
mentioning
confidence: 99%